Characteristics of Generation Z in the Utilization of Digital Storytelling Media at RSD Idaman Banjarbaru - Muhammad Zaidan; Kusnindyah Praedevy Reviagana (Salando Health Journal, 2026)
Background: Digital technology has influenced how people obtain health information. Generation Z has grown in the digital era and is familiar with the internet and social media. Health communication should align with their characteristics and preferences. Digital Storytelling (DST) integrates narrative elements with multimedia components, including images, audio, and video. This study aims to identify Generation Z patient characteristics and describe DST media utilization at RSD Idaman Banjarbaru. Methods: This study used a descriptive cross-sectional design conducted in April 2026. The population comprised 1,414 Generation Z outpatients at RSD Idaman Banjarbaru. A sample of 93 respondents was selected using purposive sampling. Data were collected through a structured questionnaire and analyzed using univariate analysis with frequency distributions and percentages. Results: Among 93 respondents, most were aged 20–25 years (82.8%), female (68.8%), residing in Banjarbaru (76.3%), unemployed (77.4%), and had senior high school or equivalent education (53.8%). Most parents worked in the non-civil service sector (81.7%). Instagram was the most-used platform (60.2%), while 55.9% spent more than 60 minutes daily on social media. Most did not follow the hospital’s Instagram account (83.9%) and had never seen its content (77.4%). Among viewers, 71.4% accessed content several times weekly. Furthermore, 79.6% perceived the hospital’s DST media as engaging and attractive. Counclusion: Generation Z patients were predominantly young adults, female, and Banjarbaru residents. Most had positive perceptions of DST media, indicating its potential as an effective medium for hospital health communication and promotion.